Is this child sick? Usefulness of the Pediatric Assessment Triangle in emergency settings - Ana Fernandez; Javier Benito; Santiago Mintegi (Elsevier, 2017)
Objective: The Pediatric Assessment Triangle is a rapid assessment tool that uses only visual and auditory clues, requires no equipment, and takes 30-60 s to perform. It's being used internationally in different emergency settings, but few studies have assessed its performance. The aim of this narrative biomedical review is to summarize the literature available regarding the usefulness of the Pediatric Assessment Triangle in clinical practice. Sources: The authors carried out a non-systematic review in the PubMed®, MEDLINE®, and EMBASE® databases, searching for articles published between 1999-2016 using the keywords "pediatric assessment triangle," "pediatric triage," "pediatric assessment tools," and "pediatric emergency department." Summary of the findings: The Pediatric Assessment Triangle has demonstrated itself to be useful to assess sick children in the prehospital setting and make transport decisions. It has been incorporated, as an essential instrument for assessing sick children, into different life support courses, although little has been written about the effectiveness of teaching it. Little has been published about the performance of this tool in the initial evaluation in the emergency department. In the emergency department, the Pediatric Assessment Triangle is useful to identify the children at triage who require more urgent care. Recent studies have assessed and proved its efficacy to also identify those patients having more serious health conditions who are eventually admitted to the hospital. Conclusions: The Pediatric Assessment Triangle is quickly spreading internationally and its clinical applicability is very promising. Nevertheless, it is imperative to promote research for clinical validation, especially for clinical use by emergency pediatricians and physicians. Resumo: Objetivo: O Triângulo de Avaliação Pediátrica é uma ferramenta de avaliação rápida que utiliza apenas pistas visuais e auditivas, não necessita de equipamentos e leva de 30-60 segundos para realização. Ele tem sido utilizado internacionalmente em diferentes configurações de emergência, porém poucos estudos avaliaram seu desempenho. O objetivo dessa análise biomédica narrativa é resumir a literatura disponível com relação à utilidade do Triângulo de Avaliação Pediátrica na prática clínica. Fontes: Realizamos uma análise não sistemática nas bases de dados do PubMed®, MEDLINE® e EMBASE® buscando artigos publicados entre 1999-2016 utilizando as palavras-chave "triângulo de avaliação pediátrica", "triângulo pediátrico", "ferramentas de avaliação pediátrica" e "departamento de emergência pediátrica". Resumo dos achados: O Triângulo de Avaliação Pediátrica demonstrou ser útil na avaliação de crianças doentes na configuração pré-hospitalar e na tomada de decisões de transporte. Ele foi incorporado, como um instrumento essencial na avaliação de crianças doentes, em diferentes cursos de suporte de vida, apesar de pouco ter sido escrito sobre a eficácia de ensino do Triângulo de Avaliação Pediátrica. Pouco foi publicado sobre o desempenho do Triângulo de Avaliação Pediátrica na avaliação inicial no departamento de emergência (DE). No DE, o Triângulo de Avaliação Pediátrica é útil para identificar, na triagem, crianças que exigem cuidado mais urgente. Estudos recentes avaliaram e provaram a eficácia do Triângulo de Avaliação Pediátrica também na identificação dos pacientes com doenças de saúde mais graves e, eventualmente, são internados no hospital. Conclusões: O Triângulo de Avaliação Pediátrica está se difundindo rapidamente de forma internacional e sua aplicabilidade clínica é muito promissora. Contudo, é essencial promover pesquisa para validação clínica, principalmente para o uso clínico por pediatras e médicos de emergência. Keywords: Pediatric Assessment Triangle, Pediatric assessment, Pediatric emergency department, Palavras-chave: Triângulo de Avaliação Pediátrica, Avaliação pediátrica, Departamento de emergência pediátrica